2018
DOI: 10.1016/j.jsps.2018.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Novel management of ovarian vein thrombosis: A case report

Abstract: Ovarian vein thrombosis (OVT) is a rare serious diagnosis especially if extending to inferior vein cava (IVC). We present a case of 36-year- old female who was diagnosed with right OVT reaching the inferior vein cava following a supra-cervical hysterectomy that was performed in the postpartum period due to excessive bleeding from uterine fibroids. Using the new generation anti-coagulant "rivaroxaban" for six months followed by maintenance regimen of aspirin and sulodexide, complete resolution of the clot was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Eight patients with OVT treated with DOACs were included in the study by Janczak et al assessing the treatment of VTE in atypical locations, 10 while 5% of 219 women with OVT included in the study by Lenz et al 74 received direct factor Xa inhibitors; however, separate outcome data were not provided. There are 3 published case reports evaluating the use of rivaroxaban 86,87 or apixaban 88 in young women with OVT, with promising results. Finally, Covut et al 89 retrospectively assessed the treatment of 36 women with OVT evaluated at the Cleveland Clinic (United States) in the years 2012‐2018.…”
Section: Ovarian Vein Thrombosismentioning
confidence: 99%
“…Eight patients with OVT treated with DOACs were included in the study by Janczak et al assessing the treatment of VTE in atypical locations, 10 while 5% of 219 women with OVT included in the study by Lenz et al 74 received direct factor Xa inhibitors; however, separate outcome data were not provided. There are 3 published case reports evaluating the use of rivaroxaban 86,87 or apixaban 88 in young women with OVT, with promising results. Finally, Covut et al 89 retrospectively assessed the treatment of 36 women with OVT evaluated at the Cleveland Clinic (United States) in the years 2012‐2018.…”
Section: Ovarian Vein Thrombosismentioning
confidence: 99%
“…Duration of treatment ranges from three to six months among authors and lifelong treatment for hypercoagulable diseases [ 7 ]. While some studies advocate the use of Vitamin K antagonists [ 5 ], others prefer low molecular weight heparin [ 11 ], although one study has demonstrated clot resolution with rivaroxaban [ 12 ]. One study showed that the treatment guidelines for lower extremity thrombosis could be extrapolated to OVT [ 13 ], and hence, our patient was prescribed apixaban for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, the British Committee for Standards in Haematology recommends the application of anti-coagulant therapy 3-6 months after diagnosed POVT. For successful treatment of the POVT, the use of LMWH and rivaroxaban over a period of six months is recommended, followed by antiagreggation sulodexide therapy to prevent the risk of relapse [13]. In patients with postpartum POVT, the use of prophylactic doses of anticoagulant drugs is advised during the next pregnancy and six weeks postpartum [14].…”
Section: Discussionmentioning
confidence: 99%